Pengaruh Citra Merek Dan Promosi Terhadap Loyalitas Pelanggan Pada Mie Densus 999 Di Samarinda - Muhammad Ridzky Kasthalani (Jurnal Administrasi Bisnis Fisipol Unmul, 2022)
Being the first step towards a predetermined goal that is starting with good discipline. There are many shortcomings in employee performance, one of which is the low level of supervision carried out by the employee leadership which is usually carried out during inspections carried out by higher leaders. Many civil servants are still busy with their own business, one of which is not coming to work which is a violation. Employees who get work performance rarely get verbal awards or promotions. When the morning ceremony few people came, many attended but few attended. This study aims to determine the work discipline of civil servants at the Citra Niaga Market office, Samarinda City. The research method used is qualitative with interview, observation, and documentation data collection techniques. The object of research is the Commercial Market of Samarinda City. The results showed that judging from all indicators, it can be concluded that the work discipline of civil servants at the Citra Niaga Market office in Samarinda City has not been running well.